Which Environmental Factors Determine Recent Cryoturbation and Solifluction Activity in a Subarctic Landscape? A Comparison between Active and Inactive Features. (21st April 2014) - Hjort, Jan
ABSTRACT Environmental factors that affect the activity‐inactivity variation of periglacial features may differ from those factors that control the distributional patterns of active features. To explore this potential difference, a statistically based modelling approach and comprehensive data on active and inactive cryoturbation and solifluction features from a subarctic area of Finnish Lapland are investigated at a landscape scale. In the cryoturbation modelling, vegetation abundance is the most important environmental variable explaining both the activity‐inactivity variation and the distribution of active sites. The next most important variables are soil moisture and (micro)climatological conditions in the activity modelling, and slope angle and ground material in the distribution modelling. For solifluction, the key variables determining the activity‐inactivity variation are mean annual air temperature and mean maximum snow depth, whereas vegetation abundance and slope angle control the distribution of active sites. Comparison between the environmental conditions of active and inactive periglacial features may provide new insights into activity‐environment relationships, which in turn are valuable when the effects of climate change on periglacial processes are explored. Copyright © 2014 John Wiley & Sons, Ltd.